The Effect of N-Hexan Extract of Sambiloto Leaf (Andrographis paniculata) on Reproduction Function of Female ICR of Mice (Mus musculus) Period of Praimplantation and Pascaimplantation - Muliana Muliana; Sukmawati Sukmawati (Bioscience, 2019)
Abstract. The objective of this research is to know the effect of giving of n-hexan extract of A. Paniculata leaf on the reproduction function on female mice and when hypodermic of how many dose of extract n-hexan most having an effect on the reproduction function on female mice. Extract gift conducted by inoculation. Mice or test animal obtained from Hall of Animal Research (BPH) of Regency Maros. Old age the mencit 10-12 week of weighing of mean body 21g, while test substance used by leaf of Andrographis paniculata obtained in regency of Bone of subdistrict of Sibulue of countryside of Pattiro Bajo. Parameter perceived that is s the number of implantation, number of life fetus, gestation loss, dead foetus, embryo resorbsi, corpus luteum, and death pascaimplantasi. This Research represent the research of experiment and desain research used that is Complete Random Device ( RAL) consisted of by three treatment group five times is restating so that obtained by fifteen combination. Result of research indicate that the gift of n-hexan extract of A. Paniculata leaf at dose level tested degrade the number of implantation, number of life fetus, improving number of gestation loss, and number of died fetus , also generate the effect fitotoksik of body weight of mice mains. From inferential research result that extract of n-hexan A. Paniculata leaf can effect on the reproduction function on female mice with the hypodermic time most having an in with day of pregnancy to-0 until pregnancy day to-4.